An unexpected distribution record of the cold water fish Pholis fangi (Pholidae) from southern Taiwan - Koeda, Keita; Muto, Nozomu (Zootaxa, 2019)
Gunnel species (family Pholidae), characterized by an elongated bar-like body and usually found in shallow coastal waters, are mostly restricted to temperate to subarctic waters in the Northern Pacific Ocean, although some in the Western Pacific are distributed southward to the northern East China Sea. Despite the absence of previous records from subtropical and tropical waters, a single specimen of the fish family Pholidae was recently trawled off southwestern Taiwan. Examination on the morphological characteristics and DNA barcoding revealed this is a Pholis fangi (Wang & Wang 1935), a species previously recorded only from cold waters in the Bohai and Yellow seas. As a consequence, the present specimen represents the first record of the species from the subtropical South China Sea coast of Taiwan, as well as an isolated southernmost record of this species, more than 1,000 km southward from the otherwise known distribution. Detailed morphology and fresh coloration are described.